2009
DOI: 10.1002/jmri.22002
|View full text |Cite
|
Sign up to set email alerts
|

Direct comparison of sensitivity encoding (SENSE) accelerated and conventional 3D contrast enhanced magnetic resonance angiography (CE‐MRA) of renal arteries: Effect of increasing spatial resolution

Abstract: Purpose: To assess the effect of attaining higher spatial resolution in contrast-enhanced magnetic resonance angiography (MRA) of renal arteries using parallel imaging, sensitivity encoding (SENSE), by comparing the SENSE contrast-enhanced (CE) MRA against a conventional CE-MRA protocol with identical scan times, injection protocol, and other acquisition parameters. Materials and Methods:Numerical simulations and a direct comparison of SENSE-accelerated versus conventional acquisitions were performed. A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…One study found that scan time for musculoskeletal exams can be reduced by half without compromising diagnostic quality [31]. SENSE is also used in MR Angiography (MRA) exams to visualize intracranial vessels [32], abdominal vasculature [3335], and peripheral vessels [36]. …”
Section: Representative Parallel Imaging Techniques: Sense Grappamentioning
confidence: 99%
“…One study found that scan time for musculoskeletal exams can be reduced by half without compromising diagnostic quality [31]. SENSE is also used in MR Angiography (MRA) exams to visualize intracranial vessels [32], abdominal vasculature [3335], and peripheral vessels [36]. …”
Section: Representative Parallel Imaging Techniques: Sense Grappamentioning
confidence: 99%
“…10) accelerations have also been shown to provide high-quality single-phase abdominal angiography. Applying SENSE in both the left-right and anterior-posterior directions necessitated a large FOV, though at the same time made it possible to (a) maintain high in-plane spatial resolution (approximately 1.0-1.5 mm 2 ) comparable to that of other renal MR angiographic techniques ( 17,18,20,33,34 ), (b) extend that spatial resolution to the section dimension with a more inclusive imaging slab than generally used, (c) maintain an image time in the 20-second range, and (d) achieve k-space traversal rates similar to those of small-FOV techniques ( 35 ). The large FOV allows for imaging of all abdominal vessels in the renal MR angiogram, which virtually eliminates the possibility of missing a renal artery origin or an accessory renal artery and provides visualization of lesions in the aorta, iliac arteries, and mesenteric arteries.…”
Section: Discussionmentioning
confidence: 99%
“…Parallel imaging (14)(15)(16) ) is a method whereby the redundancy of samples from multiple receiver coils is used to reduce the number of repetitions of the pulse sequence necessary to generate an image of a given spatial resolution. It has been applied to abdominal CE MR angiography to decrease image time (17)(18)(19), to improve spatial resolution for a given image time ( 17,18,20 ), or to improve coverage ( 21,22 ). Parallel imaging is accompanied by a loss of SNR in the resultant images, with the SNR loss worsening as the level of acceleration factor ( R ) increases.…”
Section: Discussionmentioning
confidence: 99%
“…DW echo-planar imaging acquisition can lead to imaging distortion, dropout, blurring, and signal loss. Geometric distortion and scanning time can be improved by the use of parallel imaging [25,26].…”
Section: Mri Techniquementioning
confidence: 99%
“…Recently, Bitar et al [24] described the utility of a 3D T1-weighted high-resolution technique with an 8-channel neurovascular phased-array coil. In MRA, parallel imaging (sensitivity-encoding [SENSE]) can be used to reduce the breath-hold duration, improve spatial resolution, improve venous suppression, and minimize spatial resolution loss caused by bolus profile modulation for a given scan time with appropriate triggering and 3D phase-encoding order [25].…”
mentioning
confidence: 99%